TOPICAL ADMINISTRATION OF ALOE VERA EXTRACT GEL INCREASED THE NUMBER OF MACROPHAGES AND EPITHELIALIZATION IN UVB-INDUCED SUNBURN - Tadihoedojo, Ersje Retnowati; Dharmana, Edi; Chodidjah, Chodidjah (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2019)
INTRODUCTION: The UVB exposure may cause sunburn (second degree burn). Aloe vera (AV) is widely used in wound healing, including sunburn.OBJECTIVE: To evaluate the effect of topical Aloe vera extract gel on the number of macrophages and epithelialization in UVB induced sunburn.METHODS: This posttest only-control group design used twenty female BALB/c mice with UVB-induced sunburn randomly divided into 4 groups. Control groups (Cntrl-G) were given a base gel. Group AV-25, AV-50, and AV-75 were topically treated with Aloe vera gel at the concentration of 25%, 50% and 75% respectively for 5 days. On day 5, after terminated, the samples of skin tissue were prepared for histological study using hematoxlyin eosin (HE) staining. Data were analyzed using one way ANOVA, Post-hoc LSD and Pearson correlation.RESULTS: ANOVA analysis showed that the number of macrophages and epithelialization among groups was a significantly difference (p <0.05). Post hoc analysis demonstrated that the mean number of macrophage in AV-75 (6.50), AV-50 (5.13), and AV-25 (3.93) were significantly higher compared to that of Cntrl-G (2.93). The mean of epithelialization AV-75% (25.35), AV-50 (18.15), and AV-25 (15.38), were significantly (p <0.05) higher compared to that of Cntrl-G (9.30). The Pearson correlation test indicated that there is a strong positive correlation (0.88) between the number of macrophages and epithelialization (p <0.05).CONCLUSION: The topical administration of Aloe vera gel extract for five days increased the number of macrophages and epithelialization in sunburned UVB induced sun burn.